Perkembangan Internet of Think (IOT) dan Instalasi Komputer Terhadap Perkembangan Kota Pintar di Ibukota Dki Jakarta - Subani, Muita; Ramadhan, Idrus; Sumarno, Sumarno; Syah Putra, Arman (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
This study discusses the Internet Of Think (IoT) and computer installation in the development of a smart city, a smart city that will be examined is the capital of DKI Jakarta, with the development of smart cities in Jakarta will greatly help the community in their daily activities, in this research the author examines by using the study of literature and field studies by looking directly in the field, an example of the development of an existing system is an electronic ticketing system on 2-wheeled motor vehicles, the results of this study are the results of data and proposals that will be proposed in the development of a system that will be made, hopefully it will be able to help the development of the system that will be made later in the future.